2021
DOI: 10.3892/ol.2021.12547
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits the growth of liver cancer by impairing myeloid‑derived suppressor cells in murine tumor tissues

Abstract: Curcumin, one of the active ingredients of Curcuma longa (Jianghuang), has been reported to exert multiple bioactivities, including pro-apoptotic and anti-inflammatory activities. In recent years, curcumin has been extensively studied, and it has been revealed that curcumin inhibits the growth of numerous types of cancer. However, to the best of our knowledge, the inhibitory effects of curcumin on the activation or expansion of myeloid-derived suppressor cells (MDSCs) in liver cancer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…We used 30 mg/kg 5-FU every 2 days for the 5-FU chemotherapy groups, as described in our previous study [ 7 ]. A previous study reported that up to 240 mg/kg/day is considered safe for mice [ 25 ]. In the current study, we used 100 mg/kg/day Cur for the 5-FU combination groups.…”
Section: Resultsmentioning
confidence: 99%
“…We used 30 mg/kg 5-FU every 2 days for the 5-FU chemotherapy groups, as described in our previous study [ 7 ]. A previous study reported that up to 240 mg/kg/day is considered safe for mice [ 25 ]. In the current study, we used 100 mg/kg/day Cur for the 5-FU combination groups.…”
Section: Resultsmentioning
confidence: 99%
“…The mice in the control groups were given saline at a volume equal to the treatment volume. The intervention was maintained for 14 d; the mouse body and tumor weights were regularly measured (every three days), and the tumor volume was calculated (tumor volume = length × width 2 /2)[ 25 , 26 ]. At the end of the intervention, the mice were euthanized, and the tumor tissues were removed from the mice.…”
Section: Methodsmentioning
confidence: 99%
“…Curcumin also inhibited the growth of liver cancer in vivo and in vitro via diminished expression of inflammatory factors, such as cyclooxygenase-2 (COX-2), prostaglandin E2, IL-1β, and IL-6, as well as inhibition of the TLR4/NF-κB signaling pathway. Moreover, curcumin reduced VEGF, granulocyte-colony-stimulating factor (G-CSF), and granulocyte−macrophage colony-stimulating factor (GM-CSF) ( 88 ). Additionally, curcumin decreased the migration and proliferation of non-small-cell lung cancer cell (NSCLC) cells via interfering with EGFR and TLR4/MyD88 pathways and increasing cell cycle arrest in the G2/M phase ( 89 ).…”
Section: Phytochemicals Augment Chemotherapy and Immunotherapy Throug...mentioning
confidence: 99%